Demystifying the Transformation of Bibliographic Data: Excel to MARC Decrypted - ., Duragappa; Sheshadri, K. N.; Gundur, Beeresh N. (Journal of Information and Knowledge, 2023)
This article explores the process of conversion of Excel data to MARC format, a major step in data migration which enhances the accuracy and accessibility of management of library collections. The study explains the intricacies of data curation within Excel, emphasizing the optimal structuring of information for subsequent MARC conversion. It provides an accessible introduction to MARC tags and subfield codes, essential for accurate cataloguing. The article guides readers through the steps of curating the bibliographic data in Excel and converting the curated data, mapping it to MARC tags, etc. It also delves into the crucial process of uploading MARC records into Koha, an open-source Integrated Library Management System, Furthermore, the article discovers advanced features of the MARC editor, including finding and replacing functions and deduplication, enabling global adjustments and improved data management.